Cardiopulmonary and acid-base effects of desflurane and sevoflurane in spontaneously breathing cats - Souza, A. P.; Guerrero, PNH; Nishimori, C. T.; Paula, D. P.; Santos, PSP; de Rezende, M. L.; Nunes, N. (Elsevier B.V., 2005)
The cardiopulmonary effects of desflurane and sevoflurane anesthesia were compared in cats breathing spontaneously. Heart (HR) and respiratory (RR) rates; systolic (SAP), diastolic (DAP) and mean arterial (MAP) pressures; partial pressure of end tidal carbon dioxide (PETCO(2)), arterial blood pH (pH), arterial partial pressure of oxygen (PaO(2)) and carbon dioxide (PaCO(2)); base deficit (BD), arterial oxygen saturation (SaO(2)) and bicarbonate ion concentration (HCO(3)) were measured. Anesthesia was induced with propofol (8 +/- 2.3 mg/kg IV) and maintained with desflurane (GD) or sevoflurane (GS), both at 1.3 MAC. Data were analyzed by analysis of variance (ANOVA), followed by the Tukey test (P < 0.05). Both anesthetics showed similar effects. HR and RR decreased when compared to the basal values, but remained constant during inhalant anesthesia and PETCO(2) increased with time. Both anesthetics caused acidemia and hypercapnia, but BD stayed within normal limits. Therefore, despite reducing HR and SAP (GD) when compared to the basal values, desflurane and sevoflurane provide good stability of the cardiovascular parameters during a short period of inhalant anesthesia (T20-T60). However, both volatile anesthetics cause acute respiratory acidosis in cats breathing spontaneously. (c) 2004 ESFM and AAFP. Published by Elsevier Ltd. All rights reserved.